The Effect of Semi-Refined Carrageenan and Potassium Chloride Added on Physico-Chemical Characteristics of Instant Grass Jelly - Abdul Hamid, Mansoor; Kit, Jason Chuah Wai; Devi, Mazarina; Mamat, Hasmadi; Ab Wahab, Noorakmar; Mohd. Razali, Umi Hartina; Ahmad, Fisal (Fakultas Teknik Universitas Negeri Malang, 2021)
This study focused on the effect of the combination effect of semi-refined carrageenan and potassium chloride on the instant grass jelly formulation. As in the traditional method of grass jelly production, the cornstarch was added to the grass jelly extract to give the gelling texture of grass jelly. Semi-refined carrageenan was added to replace the starch and the physicochemical characteristics and nutrient composition of the product was evaluated. The cincau leaves was boiled in a certain volume of water and the extraction was then converted to powder form via spray dryer. A pre-study has been conducted in determining the best method to produce grass jelly extract which based on the result of production yield, as well as conducted the physic-chemical tests. The finding showed that the extraction of 125g dried leaves of cincau with 4.5 L of water which boiled for 2.5 hours was the best extraction recovery with 75.92 percent. As a conclusion, SRC can be used as a starch replacer in grass jelly production as an instant product and texture is retained as well as nutrient contents of the product is improved